Fundação Nacional do Índio : um olhar sobre a atuação da Coordenação Regional de Roraima - Simões, Natasha da Fonseca da Frota (2019)
The purpose of this dissertation is to reflect the role of the National Indian Foundation (FUNAI) in the current context of public policies that deal with indigenous issues in Brazil, based on the analysis of the activities of its Regional Coordination in Roraima. All of the analysis was built on the discourses and narratives of the Foundation's civil servants and indigenous people who sought the services of the foundation, bringing the discussion about the legitimacy of their institutional role and their autonomy in the defense and protection of indigenous peoples as legal subjects. The dissertation seeks to understand the current political context in which the Foundation is inserted, as well as who are the actors and what are the interests put to the Foundation's performance, which represent the key to understanding what some political scientists call "political game”.Discourses about personal experiences and political power of the Foundation´s servants point to issues that go against the objectives of the international treaties signed by Brazil regarding Human Rights, the Federal Constitution of 1988, that is, the rights of indigenous peoples.